Analisis penyelesaian konflik agraria dengan pendekatan ekologis antara Masyarakat dengan PTPN V Sei Pagar di Desa Hangtuah Kecamatan Perhentian Raja Kabupaten Kampar - Laura Dameshita Silalahi; Zulfan Saam; Yusni Ikhwan Siregar (Jurnal Zona, 2021)
Agrarian conflicts are the result of development policies in the plantation sector. The community claims the land already planted with oil palm by the company. This research is a qualitative research using primary and secondary data. Primary data obtained from interviews with local government officials, companies and community leaders who were selected purposively at the research location. Secondary data were obtained from village offices, BPS, books, research journals related to agrarian conflicts in the plantation sector. The data collection technique used the triangulation method to obtain valid data. Furthermore, the data were analyzed descriptively. The conflict analysis method used in this study uses a problem tree so that the root of the problem and the causes and consequences of the conflict between the community and the company can be explored. The roots of the problem include the non-fulfillment of the KKPA land and a lack of understanding of land rights. This is caused by a lack of communication between the company and the community, resulting in conflicts. Efforts to resolve conflicts between companies and communities need to be carried out, especially by using an ecological approach.